PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PT. ASURANSI JIWASRAYA DI BANDAR LAMPUNG - Rina Loliyana (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
The performance of employees in the PT.Asuransi JiwaSraya (Persero)  Bandar Lampung based on several factors including leadership style, work motivation, and work environment. The purpose of this study was to determine whether leadership style, work motivation and work environment affect the performance of employees in the PT.Asuransi JiwaSraya (Persero)  Bandar Lampung. This study uses a quanitative method, namely data obtained from the results of questionnaires, with the number of samples in this study were 74 respondents with Multiple Linear Regression test, F test and R2 test with an error limit of 5% = 0.05. The results of F test calculation, the value Fcount 8.103 > 3.13 Ftable, means Ho rejected and Ha accepted.It can be concluded that the independent variables consist of leadership style (X1), motivation (X2) and the working environment (X3) simultaneously on the dependent variable that consists of employee performance (Y) to the PT.Asuransi JiwaSraya (Persero)  Bandar Lampung. Based on these results shows the results of multiple regression Y = 12.678 + 0,083X1 + 0,338X2 + 0,197X3 + 0.05.Results obtained correlation coefficient (R) of (0.508). The R2 Determination Coefficient is (0.226). This means that independent variables consisting of leadership style, employee motivation and work environment explain variation employee performance by 22.6% while the remaining 77.4% is influenced by other factors.